Modeling Reorientation Dynamics of Electrically Assisted Light-Induced Gliding of Nematic Liquid-Crystal Easy Axis - S. V. Pasechnik; A. V. Dubtsov; D. V. Shmeliova; D. A. Semerenko; V. G. Chigrinov; M. A. Sinenko; Alexei D. Kiselev (Advances in Condensed Matter Physics)
The phenomenological torque balance model previously introduced to describe the electrically assisted light-induced gliding is generalized to study the reorientation dynamics of the nematic liquid crystal easy axis at photoaligned azo-dye films under the combined action of in-plane electric field and reorienting UV light linearly polarized at varying polarization azimuth, φp. We systematically examine the general properties of the torque balance model by performing analysising the bifurcations of equilibria at different values of the polarization azimuth and apply for the model to interpret the experimental results. These involve observation of the pronounced purely photoinduced reorientation at φp≠0, as opposed to the case where the light polarization vector is parallel to the initial easy axis (φp=0), and the reorientation is almost entirely suppressed. In the regions between electrodes with nonzero electric field, the effects described by the model are that (a) the dynamics of reorientation slows down with φp and (b) the sense of easy axis rotation is independent of the sign of φp.